Cassadaga : the South's oldest spiritualist community - Guthrie, John J.; Lucas, Phillip Charles; Monroe, Gary (Florida history and culture series., 2000)
"Calling itself a "metaphysical mecca," the small town of Cassadaga, between Orlando and Daytona Beach in central Florida, was established more than a century ago on the principle of continuous life, the idea that spirits of the dead commune with the living. Though the founders of Cassadaga have passed on to the "spirit plane," the quaint Victorian town remains the oldest continuously active Spiritualist center in the South and was added to the National Register of Historic Places in 1994. While the community has often been sensationalized and misrepresented, this is the first serious work to examine its history, people, cultural environment, and religious system."--Jacket